An Analytical Study for Theses Master of Administration and Educational Planning Program at the Department of Educational Sciences at Prince Sattam Bin Abdulaziz University, Which was Licensed from 1435-1441 AH. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to identify the characteristics of master's theses in management and educational planning in the Department of Educational Sciences at the College of Education at Prince Sattam bin Abdulaziz University , depending on analyzing their methodological and objective orientations in the  light of a number of variables during the period from (1435-1441 AH), and in order  to achieve the aims of study, it has been  followed the study  of descriptive approach using the content analysis method, the study sample consisted of (37) master's theses, the study tool was a content analysis card, and the results of the study have been  showed  the following:  most of theses that have been approved considered as  the highest achievement  for the female component, And that the most targeted type of education is public education, that has been  considered , and the most researched stages of education by researchers are classified  more than one stage, and the most targeted societies are more than society,  as for the type of research, the largest percentage came In favor of quantitative research, the research method that has been most used is the descriptive one, and the sample size most chosen is from (101-300) individuals, and the most common method of testing samples is the random method, but for the most used study tools, researchers after the analysis are the questionnaire, and the most researched objective directions are issues of management and leadership in public education.                                                                                                                                In the light of the results of the study, a number of recommendations have been  recommended , the most important of which is the creation of a database containing all the abstracts of the theses that have been approved by the department and uploading those abstracts  to the department's website, allowing students to be  viewed and getting  benefits from them, and being  updated continuously